(untitled) (Pedagogical Horizons, 2025)
In light of major global challenges and the associated experiences of crisis and alienation, the question arises not only of the necessary acquisition of skills to overcome these problems, but also of educating the individual in the sense of a transformation of fundamental structures of one’s relationship to the world and to oneself (Graupe & Bäuerle, 2023; Koller, 2022; Nohl, 2021). Based on the German theory of transformational processes of Bildung (Koller, 2018, 2022), the article firstly questions whether transformation is an obligatory criterion for processes of Bildung and, secondly, suggests that reflexivity should be added as a characteristic of successful transformational processes of Bildung. Finally, the article addresses the unresolved question of how pedagogical actions can initiate, accompany and support transformational processes. In the school context, teachers should encourage students to reflect on existing routines and implicit assumptions, open up fields of experimentation and facilitate the integration and consolidation of new perspectives (El-Mafaalani, 2018; Helsper, 2004). The article provides a basis for applying the theory of transformational processes of Bildung to educational fields of action and for further theoretical development and modification if necessary.